Professional Cleaners' and Healthcare Workers' Ability to Recognize Hand Eczema - Anna Glenn Ullum; Farnam Barati Sedeh; Gregor B.E. Jemec; Kristina Sophie Ibler (Medical Journals Sweden, 2024)
Timely intervention reduces the risk of a poor prognosis in hand eczema, making early recognition of symptoms important in high-risk professions. However, limited data exist regarding the ability of cleaners and healthcare workers to recognize hand eczema. The aim of this study was to examine cleaners' and healthcare workers' ability to recognize hand eczema in clinical photographs and to assess the severity of the disease. Cleaners and healthcare workers completed a questionnaire consisting of 16 questions and participated in a structured interview referring to a validated photographic severity guide for chronic hand eczema, which comprised clinical photographs of hand eczema at varying levels of severity. Eighty cleaners and 201 healthcare workers (total N = 281) participated in the study. The rates of correctly identified hand eczema in clinical photographs (cleaners/ healthcare workers) were: 41.2%/57.7% (mild hand eczema), 81.2%/92.0% (moderate hand eczema), 85.0%/94.5% (severe hand eczema) and 82.5%/97.0% (very severe hand eczema). The proficiency of healthcare workers in recognizing hand eczema was significantly higher than that of cleaners. The results indicate that a large proportion of cleaners and healthcare workers fail to recognize mild hand eczema in clinical photographs. Healthcare workers had higher success rates in recognizing hand eczema in all severity categories. Symptom underestimation may lead to under-reporting of the true prevalence of hand eczema, with consequent loss of opportunities for prevention.